2016
DOI: 10.1002/jbmr.2814
|View full text |Cite
|
Sign up to set email alerts
|

Cbfb2 Isoform Dominates More Potent Cbfb1 and Is Required for Skeletal Development

Abstract: Cbfb is a cotranscription factor that forms a heterodimer with Runx proteins Runx1, Runx2, and Runx3. It is required for fetal liver hematopoiesis and skeletal development. Cbfb has two functional isoforms, Cbfb1 and Cbfb2, which are formed by alternative splicing. To address the biological functions of these isoforms in skeletal development, we examined Cbfb1 -/-and Cbfb2 -/-mouse embryos. Intramembranous and endochondral ossification was retarded and chondrocyte and osteoblast differentiation was inhibited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…It may partly explain why open fontanelles and sutures are prominent phenotypes in cleidocranial dysplasia, which is caused by heterozygous mutation of RUNX2 48 . High dependency on the amount of Runx2 protein among Runx family transcription factors in calvarial bone development is also shown in the comparison of Runx2 +/– mice with conditional Cbfb knockout mice or Cbfb isoform knockout mice 49 , 50 . As osteoblast progenitors were scarce and the BrdU-positive cells were few in both regions of calvaria and mandible in Runx2 −/− mice (Figs 5 and 6 ), however, our findings also indicate that Runx2 is required for the proliferation of osteoblast progenitors in both calvaria and mandible.…”
Section: Discussionmentioning
confidence: 76%
“…It may partly explain why open fontanelles and sutures are prominent phenotypes in cleidocranial dysplasia, which is caused by heterozygous mutation of RUNX2 48 . High dependency on the amount of Runx2 protein among Runx family transcription factors in calvarial bone development is also shown in the comparison of Runx2 +/– mice with conditional Cbfb knockout mice or Cbfb isoform knockout mice 49 , 50 . As osteoblast progenitors were scarce and the BrdU-positive cells were few in both regions of calvaria and mandible in Runx2 −/− mice (Figs 5 and 6 ), however, our findings also indicate that Runx2 is required for the proliferation of osteoblast progenitors in both calvaria and mandible.…”
Section: Discussionmentioning
confidence: 76%
“…There are few studies about the role of pre-mRNA alternative splicing in the differentiation of DPSCs into odontoblasts, but there are some reports on the role of pre-mRNA alternative splicing in the differentiation of osteoblasts ( 32 , 33 ). Exon 5 of CBFB, the co-transcription factor of RUNX2, is alternatively spliced to produce two subtypes, CBFB1 and CBFB2.…”
Section: Discussionmentioning
confidence: 99%
“…Exon 5 of CBFB, the co-transcription factor of RUNX2, is alternatively spliced to produce two subtypes, CBFB1 and CBFB2. Jiang et al ( 33 ) found that CBFB1 and CBFB2 played different roles in bone development, and only the deletion of CBFB2 could lead to the inhibition of osteogenic differentiation. The pre-mRNA of the transcription factor TAF4 has complex alternative splicing and can produce at least 10 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of these two mouse strains also revealed tissue-specific nonredundant functions. In addition to impaired osteoblast differentiation caused by the lack of Cbfβ2 ( Jiang et al, 2016 ), we noticed the presence of small thymi in Cbfb 2m/2m but not Cbfb 1m/1m mice ( Fig. 1 C ).…”
Section: Resultsmentioning
confidence: 89%